Pengaruh Edukasi Pencegahan Penularan Covid-19 (Jaga Jarak ) terhadap Perubahan Perilaku pada Anak di SDN 13 Telaga Biru - Mike Susianti; Anita Asih (Gorontalo Journal of Public Health, 2022)
Abstract Corona virus disease 2019 (COVID-19) is an infectious disease caused by acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The disease was first identified in December 2019 in Wuhan, the capital city of China's Hubei province, and has since spread globally. ,resulting in the ongoing 2019-2020 coronavirus pandemic. Common symptoms include fever, cough, and shortness of breath. While most cases result in mild symptoms, some progress to viral pneumonia and multi-organ failure. The research design that will be used is pre-experimental with a one group pre-post test design, sampling using Cluster Random Sampling, obtained 254 respondents aged 6-12 years. The results showed a p value of 0.000 (p <0.05) which means that there is a significant effect. It can be concluded that there is an effect of education to prevent the transmission of covid-19 (distance) on behavioral changes in children at Primary School 13 Telaga Biru.